2019
DOI: 10.2147/cmar.s232380
|View full text |Cite|
|
Sign up to set email alerts
|

<p>MiR-935 Promotes Clear Cell Renal Cell Carcinoma Migration and Invasion by Targeting IREB2</p>

Abstract: Purpose: Clear cell renal cell carcinoma (ccRCC) has the highest rate of metastasis and invasion in RCC and is the third most common adult urinary malignancy. miRNA may serve a critical role in human cancer development and progression, has been confirmed to play a pivotal role in RCC cell invasion and migration. Since miR-935 had been verified to be an oncogene or tumor suppressor in various cancers, the role of miR-935 in RCC was unclear. Methods: Real-time quantitative polymerase chain reaction (qRT-PCR) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Furthermore, miR-29a-related genetic variants alter the expression of IREB2 and may modify the risk of lung cancer together with dietary iron intake ( 79 ). Oncogenic miR-935 is elevated in renal cell carcinoma, and miR-935 directly suppresses the transcription of IREB2 by binding to the 3′-UTRs of IREB2 ( 80 ). Therefore, these miRNAs may suppress ferroptosis by targeting IREB2.…”
Section: Role Of Ncrnas In Ferroptosis and Cancer Developmentmentioning
confidence: 99%
“…Furthermore, miR-29a-related genetic variants alter the expression of IREB2 and may modify the risk of lung cancer together with dietary iron intake ( 79 ). Oncogenic miR-935 is elevated in renal cell carcinoma, and miR-935 directly suppresses the transcription of IREB2 by binding to the 3′-UTRs of IREB2 ( 80 ). Therefore, these miRNAs may suppress ferroptosis by targeting IREB2.…”
Section: Role Of Ncrnas In Ferroptosis and Cancer Developmentmentioning
confidence: 99%
“…Amounting evidence suggested that miRNAs were involved in the tumorigenesis and progression of RCC 10 . For instance, it was found that miR‐935 promoted the migration and invasion of RCC cells via regulation of IREB2 11 . In contrast, miR‐765 functioned as a tumour suppressor and inhibited formation of lipids in RCC through inhibition of PLP2 12 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs), a group of small noncoding RNAs~22-24 nucleotides in length, have been widely reported to negatively regulate their target genes at the posttranscriptional level by binding to the 3 0 UTR of target mRNAs, which play an important regulatory role in diverse cellular processes, including proliferation, apoptosis and autophagy [5][6][7]. Accumulating evidence indicates that miRNAs are aberrantly expressed in the development and progression of cancers by acting as tumor suppressors or oncogenes [8][9][10]. Recently, miR-30d-5p has been demonstrated to participate in tumor development by functioning as a tumor suppressor.…”
mentioning
confidence: 99%